Periodic Motions - Farkas, Miklós (Applied mathematical sciences (Springer-Verlag New York Inc.), 1994)
This book sums up the most important results concerning the existence and stability of periodic solutions of ordinary differential equations achieved in the twentieth century along with relevant applications. It differs from standard classical texts on non-linear oscillations in the following features: it also contains the linear theory; most theorems are proved with mathematical rigor, besides the classical applications like Van der Pol's, Linard's and Duffing's equations, most applications come from biomathematics. The text is intended for graduate and Ph. D students in mathematics, physics, engineering, and biology, and can be used as a standard reference by researchers in the field of dynamical systems and their applications.